Attitudes of small animal practitioners toward participation in veterinary clinical trials - Gruen, Margaret E. (J Am Vet Med Assoc, 2017)
OBJECTIVE: To determine attitudes of small animal practitioners toward veterinary clinical trials and variables influencing their likelihood of participating in such trials. DESIGN: Cross-sectional survey. SAMPLE: Small animal practitioners with membership in 1 of 2 online veterinary communities (n = 163 and 652). PROCEDURES: An online survey was developed for each of 2 veterinary communities, and invitations to participate were sent via email. Each survey included questions designed to collect information on the respondents’ willingness to enroll their patients in clinical trials and to recommend participation to clients for their pets. RESULTS: More than 80% of respondents to each survey indicated that they spend no time in clinical research. A high proportion of respondents were likely or extremely likely to recommend clinical trial participation to clients for their pets when those trials involved treatments licensed in other countries, novel treatments, respected investigators, or sponsoring by academic institutions, among other reasons. Reasons for not recommending participation included distance, time restrictions, and lack of awareness of ongoing clinical trials; 28% of respondents indicated that they did not usually learn about such clinical trials. Most respondents (79% to 92%) rated their recommendation of a trial as important to their client’s willingness to participate. CONCLUSIONS AND CLINICAL RELEVANCE: Participation in veterinary clinical trials by small animal practitioners and their clients and patients appeared low. Efforts should be increased to raise practitioner awareness of clinical trials for which patients might qualify. Specific elements of trial design were identified that could be modified to increase participation.